Contrasting innovation competence FINCODA model in software engineering: Narrative review - Maria-Angeles Andreu-Andres; Fernando R. Gonzalez-Ladron-de-Guevara; Amparo Garcia-Carbonell; Frances Watts-Hooge (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: Innovation competences are expected both in businesses and in higher education. Software organizations, in particular, require engineers that collaborate to deliver better services and products. Staff recruitment and training are human resource management tasks that are crucial to insuring that applicants and job holders have the competences that will facilitate quality output in software development processes.This paper seeks to determine the competences that describe high-performing, innovative professionals in software engineering in order to weigh them against the FINCODA model on innovation competences devised to assess and enhance individuals' capacity to innovate, a core outcome of the Framework for Innovation Competences Development and Assessment Project. Design/methodology/approach: A review protocol was followed to examine the literature on software engineering to identify the innovation competence and behavioral indicators that are required in individuals. Findings: According to the literature, the innovation competences required of the staff in software companies are creativity, critical thinking, initiative, team work and networking, dimensions that are contained in the FINCODA model. Findings also support the inclusion of the thirty-four behavioral indicators that constitute the five dimensions of the FINCODA model. Originality/value: Business organizations need tools to assess innovation competences in employees. Universities, as well, lack the instruments to measure development of innovation competence in undergraduates that teaching/learning methods should enhance before students reach the workplace. This research sheds light on innovative workplace behaviors of software engineers and on feasible designs of training programs for staff and undergraduates by using the FINCODA model and its behavioral indicators. Future research will focus on ratifying the validation of the model and the online assessment tool derived from it.
Keywords: 650; Innovation; competence; behavioral indicators; software engineering; narrative review; mapping review; FINCODA model